Applying legal narratives. Some comments on Bernard Jackson’s sociolinguistic approach in legal semiotics - Pieniążek, Marcin (Filozofia Publiczna i Edukacja Demokratyczna, 2019)
In the article some applications of the concept of legal narrative are undertaken in the perspective of Bernard Jackson’s legal semiotics. The analysis are developed in the perspective of Polish social and economical changes of recent decades. The leitmotif is constituted by remarks on sociolinguistic aspects of teaching legal narratives in changing reality. In this context a notion of “legal grapholect” is introduced to discuss possible influence of “deep layer” of legal language on evolving Polish lawyers’ language and vernacular. Additionally, issues of semiotic group of lawyers and legal register are discussed on the basis of the sociolinguistic paradigm. Reasoning is enriched by remarks of possible merger of Jackson’s legal semiotics and Ch. Perelman’s theory of legal argumentation.